Impacts of tourism and fire on ground-dwelling insect diversity in tropical pine forests of South Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sadapotto A, Christine SAP, Prastiyo A. 2025. Impacts of tourism and fire on ground-dwelling insect diversity in tropical pine forests of South Sulawesi, Indonesia. Biodiversitas 26: 5109-5117. Ground-dwelling insects serve as sensitive bioindicators of environmental change in tropical pine forests. This study aimed to compare the structure of ground-dwelling insect communities across three management areas of the Tala-Tala pine forest, South Sulawesi, Indonesia, namely the tourism area, non-tourism area, and post-fire area. This is the first study of ground-dwelling insect communities in Sulawesi's tropical pine forests. Sampling was conducted using multiple insect collection techniques, and ecological indices were applied to evaluate diversity, richness, evenness, and dominance. Statistical analyses were employed to compare land-use types and to assess their relationships with environmental factors. Diversity and evenness were lower in protected areas, whereas the tourism zone exhibited higher richness and dominance. Statistical analysis indicated significant (p
Keywords: Ecological indicators, fire ecology, habitat disturbance, pine forest, Sulawesi